Probabilistic slope stability analysis as a tool to optimise a geotechnical site investigation program - Zoorabadi, M; Canbulat, I; Ruest, M (APSSIM 2016: First Asia Pacific Slope Stability in Mining Conference, 2016)
Slope stability analysis is a branch of ground engineering science where there are a number of significant uncertainties. Although probabilistic slope stability analysis is an option in most commercial software, the use of this method is not common in practice. Apart from the ability of the probabilistic method to assess the impact of uncertainties on slope stability, it can also be used as a tool to optimise the geotechnical site investigation program. The first-order second-moment approximation of the Taylor series method is one of the probabilistic slope stability methods that determines the relative contribution of uncertainty projected by each component random variable. For a slope with a sequence of different geological units, each unit can be modelled as having several random variables such as cohesion and friction angle. A geological unit whose random variables are responsible for the greatest contribution to the uncertainty in the Factor of Safety (FS) will be the most controlling unit. This characteristic can be used to design geotechnical site investigation programs in order to minimise the uncertainties in these controlling units, which will enhance the Reliability Index of the computed FS. A code developed by the first author will be used in this paper to demonstrate the application of this method in to a real case study.
Keywords: slope stability analysis; probabilistic methods; first-order; second-moment approximation of Taylor series; geotechnical site investigation